2016
DOI: 10.1007/978-981-10-0740-8_1
|View full text |Cite
|
Sign up to set email alerts
|

A Battery Equalizing Scheme Using Flyback Converter and PhotoMOS Switch

Abstract: This article presents the concept of a series battery balance circuit using flyback converter to implement multiple filling valley balance. The optoelectronic switches are used as the control components for increased safety. Each battery cell has a Photo Metal-Oxide-Semiconductor Field-Effect Transistor (PhotoMOS) switch. The switch is used to determine the time at which the battery cell should be charged. The equalization current can reach 2A, hence the equalization speed is faster. The simulation and experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It also achieves the efficiency around 89% which is higher than the 80% efficiency in [19] and 80.4% in [20]. Furthermore, it can be observed from Figures 15 and 16 that this topology can achieve zero voltage turn off and zero current turn on, thus switching losses will be reduced against those [22][23][24][25][26] where soft switching cannot be achieved.…”
Section: Simulation and Experimental Verificationmentioning
confidence: 88%
See 2 more Smart Citations
“…It also achieves the efficiency around 89% which is higher than the 80% efficiency in [19] and 80.4% in [20]. Furthermore, it can be observed from Figures 15 and 16 that this topology can achieve zero voltage turn off and zero current turn on, thus switching losses will be reduced against those [22][23][24][25][26] where soft switching cannot be achieved.…”
Section: Simulation and Experimental Verificationmentioning
confidence: 88%
“…C bat,i (SOC e,i − SOC s,i ) (23) where C bat,i is the capacity of cell i. It can be observed that the balancing is finished at about 20 min, so we can take the data at 20 min as the balanced results.…”
Section: Simulation and Experimental Verificationmentioning
confidence: 99%
See 1 more Smart Citation